The Role of Hibiscus sabdariffa L. (Roselle) in Maintenance of Ex Vivo Murine Bone Marrow-Derived Hematopoietic Stem Cells - Zariyantey Abdul Hamid; Winnie Hii Lin Lin; Basma Jibril Abdalla; Ong Bee Yuen; Elda Surhaida Latif; Jamaludin Mohamed; Nor Fadilah Rajab; Chow Paik Wah; Muhd Khairul Akmal Wak Harto; Siti Balkis Budin (The Scientific World Journal)
Hematopoietic stem cells- (HSCs-) based therapy requires ex vivo expansion of HSCs prior to therapeutic use. However, ex vivo culture was reported to promote excessive production of reactive oxygen species (ROS), exposing HSCs to oxidative damage. Efforts to overcome this limitation include the use of antioxidants. In this study, the role of Hibiscus sabdariffa L. (Roselle) in maintenance of cultured murine bone marrow-derived HSCs was investigated. Aqueous extract of Roselle was added at varying concentrations (0–1000 ng/mL) for 24 hours to the freshly isolated murine bone marrow cells (BMCs) cultures. Effects of Roselle on cell viability, reactive oxygen species (ROS) production, glutathione (GSH) level, superoxide dismutase (SOD) activity, and DNA damage were investigated. Roselle enhanced the survival (P<0.05) of BMCs at 500 and 1000 ng/mL, increased survival of Sca-1+ cells (HSCs) at 500 ng/mL, and maintained HSCs phenotype as shown from nonremarkable changes of surface marker antigen (Sca-1) expression in all experimental groups. Roselle increased (P<0.05) the GSH level and SOD activity but the level of reactive oxygen species (ROS) was unaffected. Moreover, Roselle showed significant cellular genoprotective potency against H2O2-induced DNA damage. Conclusively, Roselle shows novel property as potential supplement and genoprotectant against oxidative damage to cultured HSCs.